2009
DOI: 10.1007/s12630-008-9038-x
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of antifibrinolytic drugs for on-pump cardiac surgery: a systematic review and meta-analysis

Abstract: Purpose This systematic review aimed to evaluate the efficacy and safety of topical application of antifibrinolytic drugs to reduce postoperative bleeding and transfusion requirements in patients undergoing on-pump cardiac surgery. Methods We searched The Cochrane Library, MED-LINE, EMBASE and SCI-EXPANDED for all randomized controlled trials on the topic. Trial inclusion, quality assessment, and data extraction were performed independently by two authors. Standard meta-analytic techniques were applied. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 36 publications
4
60
2
1
Order By: Relevance
“…[2], [5] The topical usage of this drug is seen in many dental, cardiac, and spinal surgeries. [21], [22], [23] Wong et al, first trialled on intraarticular administration of this drug and reported significant blood loss prevention . [2] But this trial did not have any inbuilt controls of IV TXA.…”
Section: Discussionmentioning
confidence: 99%
“…[2], [5] The topical usage of this drug is seen in many dental, cardiac, and spinal surgeries. [21], [22], [23] Wong et al, first trialled on intraarticular administration of this drug and reported significant blood loss prevention . [2] But this trial did not have any inbuilt controls of IV TXA.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of topical antifibrinolytic use in cardiac surgery (n = 622), Abrishami et al [79] found reduced postoperative blood loss and transfusion requirements in patients undergoing on-pump cardiac surgery. Mahaffey et al [80] (n = 160) found that combined intravenous and topical TXA was associated with decreased chest drain output at 3, 6 and 12 h postoperatively.…”
Section: Topical Usementioning
confidence: 99%
“…According to the data of World Health Organization (WHO) and World Bank, in 2002 wars had been among the first ten reasons which killed the most and caused disabilities. Civil losses are at the rate of 90% within all losses (1). War has many negative effects on human health.…”
Section: War and Women's Healthmentioning
confidence: 99%